La généralisation des théorèmes de Polya et V. Bernstein sur les séries de Dirichlet - Oskolkov, L. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. А. Осколков. Обобщение теоремы Полна и В. Бернштейна для рядов ДирихлеL. Oskolkovas. Polya ir V. Bernšteino teoremų Dirichle eilučių klausimu apibendrinimas